Desirable Competencies of Modern Vocational School Administrators and their Influence on Management Efficiency: A Case Study of Lampang Provincial Vocational Education Office - Buathong, Thawit; Sroypett, Juree (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
The objective study 1) to study the relationship between the desirable competencies of modern vocational education administrators and their influence on management efficiency: A Case Study of Lampang Provincial Vocational Education office, 2) to study the influence of the between the desirable competencies of modern vocational education administrators and their influence on management efficiency: A Case Study of Lampang Provincial Vocational Education office. The sample group in this study used the multistage method as follows: Cluster Sampling and data collection by the specific sampling method from the list of all educational administrators, teachers, and educational personnel under the Office of Lampang Provincial Vocational Education, 7 colleges, with a total sample of 202 people. This study using questionnaires to collect quantitative data and using correlation coefficient test and multiple regression coefficient test to test research hypotheses. The result show that: 1) The desirable competencies of modern educational administrators are at a high level and the efficiency of educational administration of the Lampang Provincial Vocational Education Office is at a high level. The correlation coefficient of the desirable Competencies of modern vocational education administrators and their influence on management efficiency has a low to moderate relationship and is positively related at the significance level of .01. The regression coefficient test found that the skills with positive coefficients as follows: 1) Entrepreneurship and Communication, 2) Specialized Thinking (Hard Skill), 3) Responsibility and Personality (Soft Skill), 4) Anticipation and Adaptation, 5) Creativity and Innovation, 6) Digital and Research-based, while 7) Mental Health Management and Self-management have negative coefficients at the significance level of .05 and .01. The estimation equation can be created as follows: Management efficiency = 0.730 +0.422ECS+0.234STS+0.197RPS+0.125AAS+0.044 CIS+0.026 DRS-1.159 MSS + 0.272